Polityczne aspekty sejmowej kontroli Rady Nieustającej – wybrane zagadnienia - Bucholc-Srogosz, Katarzyna (Przegląd Nauk Historycznych, 2012)
The paper presents study on the control functions of the Seym, but they were confined to meetings organized when the Permanent Council was working. The object of study is the control of the Permanent Council and its departments. In most cases reports of people which was delegated to evaluate the Council and its departments contained positive attitude towards the Council. However there were also negative elements, but they were given very carefully and intricately. The overt criticism was visible in speeches of opposition delegates. According to Z. Szcząski responsibility of the Council before the Parliament was illusory, even though the delegates spent most of the time on consideration of Council’s activi-ties and on discharge. The opposition attacked during assemblies the Council’s decisions, but only a small part of them were repealed. None of commissioner was brought to Seym’s trial. The paper raised the problem of constitutional and politi-cal (parliamentary) responsibility of the government. During the assemblies of 1778–1786 there were known both types of responsibility, but only in theory. The constitutional (legal) responsibility was only regulated in law in second half of eighteenth century. It seems, however, that the Parliament of Republic was not yet fully prepared to fulfill the political responsibility.